2021
DOI: 10.3390/molecules26041012
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation and Membrane Damage Mechanism of Slightly Acidic Electrolyzed Water on Pseudomonas deceptionensis CM2

Abstract: Pseudomonas is considered as the specific spoilage bacteria in meat and meat products. The purpose of this study was to evaluate the inactivation efficiency and mechanisms of slightly acidic electrolyzed water (SAEW) against Pseudomonas deceptionensis CM2, a strain isolated from spoiling chicken breast. SAEW caused time-dependent inactivation of P. deceptionensis CM2 cells. After exposure to SAEW (pH 5.9, oxidation–reduction potential of 945 mV, and 64 mg/L of available chlorine concentration) for 60 s, the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
4
5
0
Order By: Relevance
“…Figure 3 showed that the number of cells with red fluorescence greatly increased after single and combined treatments of ClO 2 and SAEW. Similar findings were also reported by Liu et al (2021), who found that SAEW‐treated Pseudomonas deceptionensis CM2 exhibited more red fluorescence than the untreated control cells and membrane damage was a key mechanism of SAEW for killing bacteria. Meanwhile, the number of red fluorescent cells in the ClO 2 + SAEW group was the most compared ClO 2 and SAEW groups.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 3 showed that the number of cells with red fluorescence greatly increased after single and combined treatments of ClO 2 and SAEW. Similar findings were also reported by Liu et al (2021), who found that SAEW‐treated Pseudomonas deceptionensis CM2 exhibited more red fluorescence than the untreated control cells and membrane damage was a key mechanism of SAEW for killing bacteria. Meanwhile, the number of red fluorescent cells in the ClO 2 + SAEW group was the most compared ClO 2 and SAEW groups.…”
Section: Resultssupporting
confidence: 89%
“…A large number of cytoplasmic substances of most cells leaked and accumulated with internal cell contents, and even broke into cell fragments and formed large clumps of bacteria. This phenomenon was supported by the results of Liu et al, who found that SAEW disrupted the cytoplasmic and cell membrane (Liu et al, 2021). For the cells in the ClO 2 + SAEW group, most S. putrefaciens cells were severely deformed, and significant morphological changes were observed, including fusion of cellular mass.…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 75%
“…Liu et al . (2021) exhibited that Pseudomonas deceptionensis was effectively inactivated by SAEW treatment and Ofori et al . (2018) confirmed that ClO 2 killed Pseudomonas aeruginosa by affecting the outer membrane and plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial test of AEW was carried out concerning the method described previously (23,24). In short, 1 mL of bacterial solution and 9 mL of treatment solution (AEW, MNZ, Lifukang) were incubated at 37 • C for 5 min, 10 min, and 20 min, respectively.…”
Section: Effect Of Aew Mnz and Lifukang On Microbiota Inactivationmentioning
confidence: 99%